Taxonomia, diversidade e prospecção do potencial xerofílico de fungos associados às angiospermas endêmicas da Antártica Colobanthus quitensis e Deschampsia antarctica - Lívia da Costa Coelho (2019)
Antarctica’s vegetation is composed by, basically, mosses, lichens and angiosperms that have adaptations to extreme conditions, mainly dehydration and low temperatures. The only two Angiosperms that were present in the Antarctic ecosystem: Colobanthus quitensis (Kunth) Bartl. (Caryophyllaceae) and Deschampsia antarctica Desv. (Poaceae) are plants considered to be cold tolerant. Agreeing with the idea that the fungi contribute to the resistance of the plant in a cold environment, the present work has as proposal the characterization of the diversity and evaluation of the xerophilic potential of the fungi isolated from C. quitensis e D. antarctica. Samples of leaves, roots and rhizosphere from both plants were collected in different places from South Shetlands Islands and in the Antarctic Peninsula. Six hundred eighty-three fungal isolates were obtained, of which 543 (79%) were represented by filamentous fungi and 140 (21%) by yeasts. The isolates were identified by molecular taxonomy and classified according to their diversity, richness and dominance. The community associated with D. antarctica showed higher values of diversity, richness and dominance between both plants. Pseudogymnoascus destructans was the only species isolated in common with D. antarctica’s samples, in all islands. Comparing the isolated taxa between both plants, 15 taxons in common were found. From the fungi recovered sistematically from leaf, roots and rhizosphere of D. antarctica, P. destructans was the only species found among them. There were no species in common isolated systematically from C. quitensis. The rhizosphere’s fungi obtained from both plants, were also used in biological essay of growth in gradual glicerol’s concentration, to evaluate the capacity of those fungi to resist to the low water availability. The taxon found more often among the xerophilic isolates was Penicillium (65 isolates), followed by Pseudogymnoascus (22). Less often were Thelebolus (2 isolates) and Leptosphaeria (1). The results obtained in this work showed that both Antarctic angiosperms shelter cold-adapted cosmopolitan fungi as well as endemic fungi, including those xerophilic capable of tolerating low water activity and with biotechnological capability to be used in the improvement of plants with economic potential regarding resistance to drought.